Syntheses and solid state structures of cyclic diynes with two chalcogen centres: a competition between weak interactions - Schulte, Jan Hilko; Werz, Daniel B.; Rominger, Frank; Gleiter, Rolf (Organic & biomolecular chemistry, 2003)
In this paper we report the synthesis of cyclic diynes of the general formula mX2n. The letters m and n indicate the lengths of chains between two CC-X units where X indicates S, Se, or Te. The lengths of the bridges vary between m = 4-8 and n = 2-6. Structural investigations by means of X-ray diffraction reveal for most systems a chair-like conformation in the solid state. For 5S22, 5S23, 7S25, 5Se22 and 5Te23 tubular structures were encountered. These structures can be traced back to weak X⋯X or weak C-H⋯π interactions.
Gesehen am 06.11.2020